Estratégias de gerenciamento de resultados e value relevance nos estágios do ciclo de vida das firmas - Ribeiro, João Paulo Machado (2021)
This study investigates how the relationship between the use of earnings management strategies and the value-relevance of accounting information is associated with the stages of a firm's life cycle. A sample of non-financial companies listed on B3 S/A - Brazil, Bolsa, Balcão for the 2010-2018 period was analyzed, with data collected from Refinitiv®. The GRA and GRDO proxies were estimated, respectively, using the Model of Pae (2005) and Roychowdhury (2006). In addition, an adaptation of the value-relevance model proposed by Ohlson (1995) was used, as well as the Park and Chen (2006) model, which was used to classify the stages of the life cycle. Regarding the analysis methods, multiple linear regression and quantile regression models were used. The results show that, compared to Maturity companies, Growing companies are associated with higher levels of negative discretionary accruals and smaller cuts in discretionary expenses, while Declining companies are more likely to use accounting choices to increase profits as well as cutting discretionary expenses. The analysis of value-relevance models indicates that the value-relevance of earnings is negatively affected when GRA is used to increase earnings and when GRDO decreases current earnings. As for the life cycle reflections in this relationship, it is highlighted that, for Growing companies, a high level of GRA was associated with an increase in the value-relevance of earnings, whereas for companies in Decline, the use of GRDO to increase the results are associated with a significant loss in the value-relevance of earnings. Thus, the study contributes with evidence that investors attribute lower value relevance to company profits as a greater probability of engaging in earnings management strategies only in certain settings, which may suggest that this is not being perceived by investors in all of the contexts. Others who will possibly benefit from the study's findings are auditors and financial analysts, who can use insights into the tendency to adopt certain earnings management strategies given the firm's life cycle stage when analyzing the companies' accounting information.